Regulating Indonesian Tax Consultant Profession: Is it Necessary? - Nasrullah Nasrullah; Putri Anggia (Fakultas Hukum Universitas Muhammadiyah Magelang, 2020)
The decision of the Constitutional Court of the Republic of Indonesia (MK RI) Number 63 / PUU-XV / 2017 encourages the formation of laws and regulations regarding tax consultants. However, when viewed in the minister of finance regulation, the tax consultant profession is not implicitly accommodated. This study analyzes the Tax Consultant profession's position in the Indonesian legal system and the future direction after the Constitutional Court Decision Number 63 / PUU-XV / 2017. This research was conducted through a combination of a normative and empiric juridical method. Interviews were conducted with the Directorate General of Taxes at the Ministry of Finance of the Republic of Indonesia and a professional tax consultant to strengthen the arguments. The analysis was carried out in a descriptive qualitative manner. The results showed that the regulation of the tax consultant profession is generally regulated in law. However, this provision does not provide a comprehensive and appropriate legal framework to organize a professional and independent tax consultant. For this reason, in order to provide legal certainty for Tax Consultants and Taxpayers, it is necessary to have a specific law regulating tax consultants in Indonesia. The Tax Consultant Law can serve as a legal umbrella for professional tax work. The government must comprehensively regulate, among others, the rights and obligations of a tax consultant, the scope of duties and powers of a tax consultant, as well as the establishment of a tax consultant organization